Volcanic Lateral Collapse Processes in Mafic Arc Edifices: A Review of Their Driving Processes, Types and Consequences - Romero, Jorge E.; Polacci, Margherita; Watt, Sebastian; Kitamura, Shigeru; Tormey, Daniel; Sielfeld, Gerd; Arzilli, Fabio; La Spina, Giuseppe; Franco, Luis; Burton, Mike; Polanco, Edmundo (Frontiers in Earth Science, 2021)
Volcanic cones are frequently near their gravitational stability limit, which can lead to lateral collapse of the edifice, causing extensive environmental impact, property damage, and loss of life. Here, we examine lateral collapses in mafic arc volcanoes, which are relatively structurally simple edifices dominated by a narrow compositional range from basalts to basaltic andesites. This still encompasses a broad range of volcano dimensions, but the magma types erupted in these systems represent the most abundant type of volcanism on Earth and rocky planets. Their often high magma output rates can result in rapid construction of gravitationally unstable edifices susceptible both to small landslides but also to much larger-scale catastrophic lateral collapses. Although recent studies of basaltic shield volcanoes provide insights on the largest subaerial lateral collapses on Earth, the occurrence of lateral collapses in mafic arc volcanoes lacks a systematic description, and the features that make such structures susceptible to failure has not been treated in depth. In this review, we address whether distinct characteristics lead to the failure of mafic arc volcanoes, or whether their propensity to collapse is no different to failures in volcanoes dominated by intermediate (i.e., andesitic-dacitic) or silicic (i.e., rhyolitic) compositions? We provide a general overview on the stability of mafic arc edifices, their potential for lateral collapse, and the overall impact of large-scale sector collapse processes on the development of mafic magmatic systems, eruptive style and the surrounding landscape. Both historical accounts and geological evidence provide convincing proofs of recurrent (and even repetitive) large-scale (>0.5 km3) lateral failure of mafic arc volcanoes. The main factors contributing to edifice instability in these volcanoes are: (1) frequent sheet-like intrusions accompanied by intense deformation and seismicity; (2) shallow hydrothermal systems weakening basaltic rocks and reducing their overall strength; (3) large edifices with slopes near the critical angle; (4) distribution along fault systems, especially in transtensional settings, and; (5) susceptibility to other external forces such as climate change. These factors are not exclusive of mafic volcanoes, but probably enhanced by the rapid building of such edifices.